Restorative museum environments: emotional coping strategies for people living with chronic multimorbidity - Mao, Keren; Qian, Sijin (Frontiers in Psychiatry, 2025)
ObjectiveWith the growing population of individuals suffering from chronic disease comorbidities, mood disorders have emerged as a critical factor adversely impacting their quality of life. As a potential form of restorative environmental intervention, museum spaces possess unique advantages in fostering emotional recovery and providing mental health support. This study aims to explore museum design strategies grounded in restorative environmental therapy to enhance emotional regulation experiences for patients with chronic comorbidities.MethodsThis research integrates the Kano model, Quality Function Deployment (QFD), and the Pugh Matrix (Platts’ Matrix) to systematically identify, classify, and prioritise the emotional regulation needs of patients with chronic comorbidities within the context of museum environments. By establishing a mapping relationship between the characteristics of healing environments and specific spatial design elements, the study develops a structured design framework tailored to emotionally supportive museum spaces.ResultsFindings indicate that museum designs optimised through principles of healing environment therapy significantly enhance emotional recovery in patients with chronic comorbidities. Improvements were observed in aspects such as spatial layout, sensory stimulation, user interaction, and perceived sense of belonging. Compared to conventional museum spaces, the optimised designs yielded higher emotional regulation scores and markedly reduced indicators of anxiety, loneliness, and mood instability.ConclusionThis study confirms the efficacy of healing environment-based design strategies in museum settings for regulating the emotional states of patients with chronic comorbidities. It proposes actionable design interventions and strategic pathways that offer both theoretical foundations and practical guidance for the future development of health-promoting public spaces. Moreover, it broadens the application of restorative environmental therapy within the cultural sector.